Democracy and its limits: lessons from Asia, Latin America, and the middle East - "Handelman, Howard (ed.)" (Notre Dame, 1999)
Eleven papers drawn from a May 1997 conference of the same name (sponsored by the U. of Wisconsin's Center for Latin America and Center for International Studies) are presented by Handelman (political science, U. of Wisconsin) and Tessler (political science, U. of Arizona). Somehow managing to avoid a detailed discussion of U.S. foreign policy, the papers discuss structural and cultural factors that limit progress towards procedural democracy in different parts of the world. Specific countries examined include China, Korea, Brazil, the Philippines, and Mexico, while other contributions discuss regional characteristics of Latin America, the Middle East, and elsewhere.
Keywords: Democracy-Developing Countries